1997
DOI: 10.1007/s004270050128
|View full text |Cite
|
Sign up to set email alerts
|

Surface mesoderm in Xenopus : a revision of the stage 10 fate map

Abstract: We have used two complementary cell labeling techniques to investigate dorsal mesoderm formation in Xenopus laevis and Hymenochirus boettgeri. Epithelial grafts from fluorescently labeled donors into unlabeled hosts demonstrate that in Xenopus, as previously shown for Hymenochirus, superficial cells of the dorsal marginal zone have the ability to invade the notochord and somite and participate in their normal morphogenesis, in a stage-specific and region-specific manner. A new method for superficial fate mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 51 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Albino embryos were labelled with active biotin essentially as previously described (Minsuk and Keller, 1997). Embryos were dejelleyed 30 min after fertilisation and placed in 10 mg/ml Sulfo-NHS-LC-Biotin (Pierce) in 0.1· MMR for 30 min.…”
Section: Biotin Labellingmentioning
confidence: 99%
“…Albino embryos were labelled with active biotin essentially as previously described (Minsuk and Keller, 1997). Embryos were dejelleyed 30 min after fertilisation and placed in 10 mg/ml Sulfo-NHS-LC-Biotin (Pierce) in 0.1· MMR for 30 min.…”
Section: Biotin Labellingmentioning
confidence: 99%
“…6B; t ϭ 350 min). Work by Minsuk and Keller (1997) showed that the presence of these ingressing cells is highly variable between embryos and along the anteroposterior axis, with a greater proportion of them present toward the posterior end of the axis. Given this variable population of ingressing cells, it may be the case that they are involved in the gradual increase in the rate of somite rotation observed along the anteroposterior axis.…”
Section: Differences In Somite Morphogenesis Along the Anteroposteriomentioning
confidence: 99%
“…Apart from their role in shielding the embryo from the exterior, superficial cells differ from deep cells in many other ways. Superficial and deep cells do not mix until later in development (Keller, 1978;Smith and Malacinski, 1983;Hartenstein, 1989;Minsuk and Keller, 1997) and they follow different cell fates, express different genes and have different roles in gastrulation (Keller, 1975;Minsuk and Keller, 1997;Keller, 1976;Shih and Keller, 1992;Keller et al, 1985;Glinka et al, 1996;Smith et al, 1995;Sive and Bradley, 1996;Deblandre et al, 1999). Thus, the formation of an outer epithelial cell layer and one or more, internal non-epithelial cell layers, and the developmental distinction between them, is one of the fundamental differentiations in the early embryo.…”
Section: Introductionmentioning
confidence: 99%